2021
DOI: 10.1186/s13054-021-03495-8
|View full text |Cite
|
Sign up to set email alerts
|

Drug dosing in the critically ill obese patient: a focus on medications for hemodynamic support and prophylaxis

Abstract: Medications used for supportive care or prophylaxis constitute a significant portion of drug utilization in the intensive care unit. Evidence-based guidelines are available for many aspects of supportive care but drug doses listed are typically for patients with normal body habitus and not morbid obesity. Failure to account for the pharmacokinetic changes that occur with obesity can lead to an incorrect dose and treatment failure or toxicity. This paper is intended to help clinicians design initial dosing regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 71 publications
0
13
0
Order By: Relevance
“…However, the use of an ideal or adjusted weight is suggested for weight-based dosing in obese patients with BMI of 40 kg/m2 or greater is recommend for methylprednisolone for patients with ARDS. 20 Regardless, the dosing of corticosteroids should be adjusted based on patientspecific factors. 13 Comparison of literature supporting the use of corticosteroids in severely ill mechanically ventilated COVID-19 patients being treated with corticosteroids Recognizing the importance of corticosteroids in treating COVID-19, the research and investigation of corticosteroids for severe COVID-19 patients launched worldwide.…”
Section: Obesity Dosing Of Corticosteroidsmentioning
confidence: 99%
“…However, the use of an ideal or adjusted weight is suggested for weight-based dosing in obese patients with BMI of 40 kg/m2 or greater is recommend for methylprednisolone for patients with ARDS. 20 Regardless, the dosing of corticosteroids should be adjusted based on patientspecific factors. 13 Comparison of literature supporting the use of corticosteroids in severely ill mechanically ventilated COVID-19 patients being treated with corticosteroids Recognizing the importance of corticosteroids in treating COVID-19, the research and investigation of corticosteroids for severe COVID-19 patients launched worldwide.…”
Section: Obesity Dosing Of Corticosteroidsmentioning
confidence: 99%
“…Regarding corticosteroids, a recent literature review suggested using the same dose of hydrocortisone in obese and non‐obese patients for non‐weight‐based dosing of hydrocortisone in patients with community‐acquired pneumonia or septic shock unresponsive to fluids and vasopressors. In patients with acute respiratory distress needing methylprednisolone, the authors instead suggested using weight‐based dosing based on the ideal or adjusted body weight 11 . Very few pharmacokinetic (PK) studies involving DEX or other corticosteroids have been conducted in obese patients 13 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, in a study of 100 injectable medications commonly used in an ICU, only 30% of drug labels had a specific weight descriptor in the labeling information 10 . The use of an incorrect weight metric for dosing could lead to treatment failure or drug toxicity 11 . The altered pathophysiology of the obese body may also affect drug distribution in tissues and drug elimination 12 …”
Section: Introductionmentioning
confidence: 99%
“…Pharmacokinetic and clinical data have supported dose adjustments of certain medications, such as enoxaparin, etomidate, and ketamine for the obese patient. 8,9 However, dosing recommendations are lacking for antipsychotics and benzodiazepines when used for agitation. To our knowledge, no clinical studies have evaluated the optimal dosing of agitation medications in the obese population.…”
mentioning
confidence: 99%
“…Obesity is prominent in the US population and poses significant concerns as it relates to optimal medication dosing. Pharmacokinetic and clinical data have supported dose adjustments of certain medications, such as enoxaparin, etomidate, and ketamine for the obese patient 8,9 . However, dosing recommendations are lacking for antipsychotics and benzodiazepines when used for agitation.…”
mentioning
confidence: 99%